Cryptocurrency dalam Perspektif Hukum Islam: Studi Komparatif Metode Istinbāṭ MUI dan Dār al-Iftā' al-Miṣriyyah dalam Kerangka Maqāṣid al-Sharī'ah - Muhammad Anugrah Izzul Haq; Muhammad Zidan Irfani; Firdah Nailil Karimah (Syariah: Journal of Fiqh Studies, 2026)
The growth of the digital economy has introduced cryptocurrency as a novel financial instrument demanding normative responses from Islamic legal authorities. This study aims to comparatively analyze the methods of legal reasoning (istinbāṭ) employed by the Indonesian Council of Ulama (MUI) and Dār al-Iftā' al-Miṣriyyah in issuing fatwas on cryptocurrency within the framework of maqāṣid al-sharī'ah, while identifying the determinant factors underlying their methodological divergences. A qualitative approach with a comparative research design was employed through library research. Primary data were drawn from official fatwa documents of both institutions, supplemented by secondary sources including uṣūl al-fiqh literature, fiqh al-muʿāmalāt texts, and peer-reviewed journals. Data were analyzed through content and comparative analysis. Findings reveal that MUI applies Tahqīq al-Manāṭ, yielding a graduated fatwa that conditionally permits cryptocurrency as a tradable commodity (sil'ah) under specific Shariah parameters, while Dār al-Iftā' al-Miṣriyyah employs Sadd al-Żarī'ah, resulting in an absolute prohibition. These divergences are shaped by national regulatory frameworks, dominant jurisprudential traditions, institutional relations with the state, and socioeconomic contexts. Within the maqāṣid al-sharī'ah framework, both approaches represent legitimate variants in realizing ḥifẓ al-māl, albeit through diametrically opposed strategies. This study contributes theoretically to contemporary fatwa methodology discourse and practically offers recommendations for harmonizing digital asset fatwa standards at the international level.